Education Programs in the Prevention of Sexually Transmitted Diseases in Adolescents - Roselina, Elsa; Muhammad, Rosmaliza (Qualitative and Quantitative Research Center, 2023)
Health education is an effective way to increase teenagers' knowledge about reproductive health and sexually transmitted diseases. Teenagers' permissive attitude toward unrestricted sexual conduct is backed by their low awareness about adolescent reproductive health. This article aims to determine educational programs in preventing sexually transmitted diseases. This article uses qualitative methods through a literature review approach. The data in this research are articles from Google Scholar sourced from journals published in 2022 and 2023, with the authors from Indonesia and Malaysia. The results found that many teenagers were sexually active, although not always of their own free will. In some developing countries, about half of them are married. Irresponsible early sexual activity puts teenagers at risk of various reproductive health education challenges. The conclusion is based on the results of the analysis of this literature review. Adolescents' awareness of the dangers of unsafe sexual behavior has increased, indicating the effectiveness of preventive messages. The education program has succeeded in involving the community, including parents, teachers, and other interested parties, in supporting efforts to prevent sexually transmitted diseases among adolescents. The contribution of this research is to provide an overview of the educational programs in preventing sexually transmitted diseases and provide information on the evil influence of sexually transmitted diseases on adolescents.